2017
DOI: 10.3390/microorganisms5030062
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Endotracheal Aspirates Sonication on Ventilator-Associated Pneumonia Microbiologic Diagnosis

Abstract: Microorganisms are able to form biofilms within respiratory secretions. Methods to disaggregate such biofilms before utilizing standard, rapid, or high throughput diagnostic technologies may aid in pathogen detection during ventilator associated pneumonia (VAP) diagnosis. Our aim was to determine if sonication of endotracheal aspirates (ETA) would increase the sensitivity of qualitative, semi-quantitative, and quantitative bacterial cultures in an animal model of pneumonia caused by Pseudomonas aeruginosa or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This might be biased by the generally higher prevalence of non-mucoidal strains in CF patients which is in agreement with the study of Adkin et al [48]. However, the acquisition of the resistance particularly to colistin, tobramycin, meropenem, and ciprofloxacin by nonmucoid P. aeruginosa strains was previously related to suppressive antimicrobial therapy in chronically infected CF patients by Fernandez-Barat et al [49]. A weak correlation between colistin, tobramycin, and ciprofloxacin found in our study was confirmed by other authors who characterized the additivity effect of ciprofloxacin/colistin and tobramycin/colistin combined therapy [50,51].…”
Section: Discussionsupporting
confidence: 85%
“…This might be biased by the generally higher prevalence of non-mucoidal strains in CF patients which is in agreement with the study of Adkin et al [48]. However, the acquisition of the resistance particularly to colistin, tobramycin, meropenem, and ciprofloxacin by nonmucoid P. aeruginosa strains was previously related to suppressive antimicrobial therapy in chronically infected CF patients by Fernandez-Barat et al [49]. A weak correlation between colistin, tobramycin, and ciprofloxacin found in our study was confirmed by other authors who characterized the additivity effect of ciprofloxacin/colistin and tobramycin/colistin combined therapy [50,51].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, microbiologic criteria are also an important element for VAP in a clinical context, such as positive culture results from suctioned sputum, bronchoscopy, blind bronchoalveolar lavage (BAL), or pleural fluid. Although not required to diagnose VAP, serial cultures and microscopic assessments of tracheal aspirate samples during treatment can be useful gauges of the patient’s response to antibiotics (Mariki et al, 2014; Fernandez-Barat et al, 2017). VAP can also be divided into early- and late-onset VAP.…”
Section: Definition and Diagnosis Of Vapmentioning
confidence: 99%
“…To differentiate between colonization and infection, the quantification of colony forming units (CFU) per milliliter was used. The BA/BAL cultures were considered positive if there was growth of >10 5 CFU/mL for BA, and >10 4 CFU/mL for BAL [55][56][57].…”
Section: Microbiological Studymentioning
confidence: 99%